PENDAMPINGAN PEMBELAJARAN DENGAN PARADIGMA BARU BAGI SEKOLAH PENGGERAK TERKAIT ASESMEN PEMBELAJARAN DI UPT SD NEGERI 211 GRESIK - Ismail Marzuki; M. Luthfi Oktarianto (LP4MK STKIP PGRI Lubuklinggau, 2022)
As the Merdeka Learning Campus Merdeka program was rolled out by the Ministry of Education, Culture, Research, Technology, and Higher Education, schools had to master many new things. The new things include a paradigm shift in learning, liberating education, projects to strengthen the profile of Pancasila students, differentiated learning, and learning assessments. Since the program was initiated, the Ministry has made various breakthroughs including conducting socialization, training, training, technical guidance, and mentoring. However, at the implementation level, not all programs went according to plan, because various problems were found in them. These problems include technical related issues, such as making the Education Unit Operational Curriculum (KOSP), making teaching modules, differentiated learning, and learning assessments. Regarding this problem, the solution offered is to provide assistance to educators and school principals. The implementation step is to provide assistance and workshops to them. The result is that educators gain new insights into the development of assessment instruments using a new paradigm for sekolah penggerak. The team recommends the need to make a follow-up plan related to mentoring learning with a new paradigm.